A Limited Fixation, Olecranon Sparing Approach, for Management of Geriatric Intra-Articular Distal Humerus Fractures. (12th August 2020) - Kaiser, Philip B.; Newman, Erik T.; Haggerty, Christopher; Appleton, Paul T.; Wixted, John J.; Weaver, Michael J.; Rodriguez, Edward K.
Purpose: We propose that geriatric comminuted intra-articular distal humerus fractures can be effectively treated with a limited fixation approach aimed at achieving varus/valgus stability with columnar fixation, but allowing intra-articular comminution to heal by secondary congruency against an intact olecranon, thus avoiding an olecranon osteotomy. Methods: Fifty-six elderly patients with AO 13-C type fractures, who underwent surgical fixation with ≥12-months of follow-up were retrospectively reviewed. Thirty patients were treated with intra-articular open reduction internal fixation (ORIF) with an olecranon osteotomy and 26 patients were treated with our limited fixation (L-ORIF) approach. Outcomes were range of motion (ROM), complications, additional surgery, and patient-reported outcome measures (PROMIS). Results: At final follow-up, the average elbow ROM was 97° (40°-155°) in the ORIF group and 86.5° (20°-145°) in the L-ORIF group. There was a trend toward more complications and additional surgery in the ORIF group. PROMIS scores for pain were 53.1 and 52.14, and PROMIS functional scores were 41.7 and 41.4 in the ORIF and L-ORIF group respectively. No differences in outcomes were statistically significant. Conclusion: A limited fixation technique based on achieving varus/valgus stability with columnar fixation, demonstrated equivalent outcomes in elderly patients with intra-articular distal humerus fractures when compared to intra-articular ORIF with an olecranon osteotomy